Measurement and analysis of the lowest resonant mode of a spherical annular‐sector patch antenna. Issue 2 (1st January 2015) - Weiss, Steven; Cohl, Howard; Boliong, Amang
Abstract : The cavity model for patch antennas has been used extensively since 1970s. This model gives excellent first‐order estimates for the antenna's internal fields near any resonant frequency. Although frequently used for planar geometries, there is no reason why the model cannot be employed for other geometries. This study discusses some of the complexities in selecting the correct pair of linearly independent associated Legendre functions when attempting to employ the cavity model using a spherical annular‐sector patch antenna.